‘Lely-wyte, clene with pure virginyté’: The N-Town 'Nativity', the Virgin Mary, and Trans Misogyny - Rivkin, Nat (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2024)
This article examines how the Virgin Mary’s immaculate childbirth in the N-Town ‘Nativity’ illuminates recent scholarship on trans misogyny. I argue that the N-Town ‘Nativity’ diagnoses Mary’s enduring virginity after childbirth as itself a form of gender variance, and the play punishes the doubtful midwife Salomé for her lack of faith in another’s claim to womanhood. Moreover, this early Christian drama allows scholars today to contest the hostile myth that trans misogyny is at once natural and biblically sanctioned. Mary’s durable yet opaque virginity generates the anatomical scrutiny too often evoked by contemporary trans femininities.